Diagnosing pediatric intussusception through bedside ultrasound by novice emergency department sonographers: a case report - Farah NA,; Ismail Mohd Saiboon, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Intussusception is a common cause of gastrointestinal emergency in the paediatric population and it is usually diagnosed through Barium enema radiography or ultrasound. The skill of using an ultrasound by a minimally trained medical officer in diagnosing this cases in the Emergency Department are very helpful and expedite the management. We present the case of a 7-month-old girl who presented to Emergency Department (ED) with the chief complaint of passing blood in stool. Clinically she was dehydrated, irritable and in compensated shock. There was generalised tenderness per abdomen but it was soft and not distended. There was no palpable mass and bowel sound normal. Immmediate fluid resuscitated commenced. Bedside abdominal ultrasound performed by ED medical officer showed a 1.8 cm x 2.5 cm mass of alternating hypo-echoic and hyper-echoic rings at the right lower quadrant, consistent with the ‘target’ sign of intussusception. Supine plain abdominal X-ray did not reveal any abnormality. The ultrasound finding of intussusception was later confirmed by the radiologist. She underwent immediate hydrostatic reduction and was discharged well.